Design, Development and Evaluation of Self Nanoemulsifying Drug Delivery System of Garlic Oil using Capryol PGMC - Sangar, Priyanka; Sandip, Bandgar; Sardar, Shelake; Pravin, Patil; Durgacharan, Bhagwat; Shitalkumar, Patil (Indian Journal of Pharmaceutical Education and Research, 2019)
Introduction: At present days there was considerable attention has been taken to develop lipid based pharmaceutical preparation which improves solubility as well as permeability leads to improve oral bioavailability of poorly water soluble drug with a system known as self nano-emulsifying drug delivery system. Materials and Methods: The SNEDDS of garlic oil was prepared by using oleic acid as oil, capryol PGMC as a surfactant and ethanol as a co-surfactant, as the garlic oil shows better solubility in these excipients which is find out by constructing pseudo-ternary phase diagram. The Km=3 was selected for the preparation of SNEDDS of garlic oil because it shows better nanoemulsion region as compared to Km=1 and 2. Discussion: The formulated SNEDDS of garlic oil was evaluated for physical characterization, thermodynamic stability, rheology study, globule size and zeta potential, dispersibility study, cloud point determination, % transmittance, drug content, FTIR study and in vitro drug release study. Three batches of SNEDDS of garlic oil was formulated using Km value 3 which cover maximum nanoemulsion region, containing oleic acid (solubility 57.53± 0.45), Capryol PGMC (solubility 59.80±0.82) and ethanol (solubility 49.83± 0.30). Based on the compatibility study, optimum globule size (177.2 nm), minimum polydispersity (0.386), higher drug content (90.89 ± 0.68) and higher drug release (98.85%), batch F2 was optimized. Conclusion: The bioavailability problem can be overcome by the Self nano- emulsifying drug delivery system, which presents the more drug in solubilized form in the body as compared with other conventional drug delivery systems.
Keywords: Self Nanoemulsifying Drug Delivery System; Garlic oil; Pseudo ternary phase; diagram; Capryol PGMC; poorly water soluble drug